About Voices and Silences. Writings and Reflections on the Inquiry into the Learning of Young Students in Different Contexts (Revista Peruana de Investigación Educativa, 2011)
The work reflects upon two research lines being carried out in Argentina in a research programme: On the one hand, it focuses on studying the particular characteristics in which students build up their learning within school and out-of-school contexts; on the other hand, although closely related to this, it focuses on highlighting the students’ voices according to a theoretical and methodological tradition which attempts to position students actively in educational research. Within a cualitative etnographical approach, the research team developed a “learning diary” with students’ groups of a Secondary School. Students’ feelings, emotions, thoughts, voices, and silences become outstanding and key factors around school and out-of-school learning processes.
Keywords: Secondary School; learning context; educational research; pupil-school relationship; out-of-school education